Adolescents' dietary polyphenol intake in relation to serum total antioxidant capacity: the HELENA study. (2nd January 2022) - Wisnuwardani, Ratih W.; De Henauw, Stefaan; Forsner, Maria; Gottrand, Frédéric; Huybrechts, Inge; Kafatos, Antonios G.; Kersting, Mathilde; Knaze, Viktoria; Manios, Yannis; Nova, Esther; Molnár, Dénes; Rothwell, Joseph A.; et al.
Abstract: We evaluated the association between intake of total polyphenols, polyphenol classes and the 10 most consumed individual polyphenols with serum total antioxidant capacity (TAC) in 749 European adolescents (53% girls; 15% overweight; 12.5–17.5 years-old) from the cross-sectional HELENA study of 2006–2007. Dietary polyphenol intake was calculated from two non-consecutive 24-h recalls matched with the Phenol-Explorer database. Multilevel linear models examined the associations between dietary polyphenols and TAC. Polyphenol intake was rather low (median = 321mg/day; p25 = 158; p75 = 536) and TAC was comparable to other literature findings (median = 1.57 mmol/L; p25 = 1.45; p75 = 1.74). Total polyphenol intake, polyphenol classes and the top 10 compounds were not associated with TAC in a linear, quadratic or cubic way in partially or fully confounder-adjusted models. A direct anti-oxidative effect of dietary polyphenol intake was not observed in European adolescents. Polyphenol biomarkers and additional antioxidant measures are needed in future prospective studies to confirm these results.